Aplicações cotidianas das cônicas: uma proposta de sequência didática sob a perspectiva da pedagogia histórico-crítica - (:unkn) unknown (Universidade Federal do Recôncavo da Bahia, 2024)
The conics, since Apolônio’s study to the comtemporany analistic’s conceptions, perform a important perfil to the comprehension of a lot of areas of knowing. This work intend fortify the process of teaching-learning across a bibliography of concepts and a teory who relation the conics. Will be highlighted your history importance, analytical geometry relevance and the presentantion of fundamental theorems that deepen the understanding of these curves. Moreover, will be propoused a didactics sequence, based on the assumption from the history critic pedagogy, finding an efficiency and acessibility to the students and teachers from basic education. Will be discussion the pratic enforcement from the conics in the daily, finding promove a learning, encouraging a explore of this curves with experimentation and logical reasoning. Is expected the study help from the development of strategies for the conic’s teaching, enable the students with the necessary tools for comprehension and apliccation of this concepts with a significative way in the social pratics.
Keywords: Conics; Cônicas; Analytical geometry; Geometria Analítica; Didatic sequence; Sequência Didática; Historical pedagogy; Pedagogia Histórico; Critical; Crítica; Análise Matemática.